Continuing Professional Development a Vocational Education Teacher in West Java - Mulyadi, Yadi; Sumarto, Sumarto; Maknun, Johar (INVOTEC, 2017)
Continuous professional development of vocational teachers is a strategic effort to increase the competence of professional vocational teachers in a planned and structured. Professional vocational teachers have mastery of competencies demands a comprehensive multi-dimensional. Competency professional standards based on juridical regulation, which includes professional competence, personal competence, social competence and ped-agogical competence. Multi-professional competence of vocational teachers increasingly complex, because the substance of technological and vocational extremely varied and has very wide dimensions. The dynamics of technological and vocational education has a high acceleration, in line with the development of business and industry. The substance of the subject matter and learning model developed adaptive and portable, so as to synchronize the changes that occur. This paper will identify a comprehensive identity-based teacher professional culture-based model 'Raymond Gagnon'. Teacher professional identity associated with the technical efforts undertaken vocational teachers in West Java in an effort to improve the mastery of basic prerequisite's professional teacher competency standards. Descriptive analysis was conducted to describe the specific technical efforts in improving professional skills had been done, either individually, or in groups of formal institutions. The final result can be seen mapping profile in a structured continuous professional development and conceptual provide strategic impact to the renewal of knowledge and the improvement of teaching practices in the classroom teacher. Implications of the study of the issue of continuing professional development provide a conceptual input to various relevant parties on the professional development of vocational teachers in a more comprehensive, systemic and structured